Studies on Nephroprotective effect of Methanolic and Aqueous Extract of Bark of Pithecellobium Dulce Roxb. in Rats. (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Kidney failure is a major problem of worldwide proportions. Kidney injury is a sudden loss of kidney function resulting in the accretion of waste materials such as creatinine and urea in the body. There are various agents that exert nephrotoxic effects through distinctive morbific defence mechanisms. Gentamicin, cisplatin and paracetamol are among common nephrotoxicity agents. In recent years, natural compounds are being expanded used in the treatment of kidney diseases. With this backdrop the study has been designed with the aim to studies on nephroprotective effect of methanolic and aqueous extract of bark of Pithecellobium Dulce Roxb. in rats. The methanolic and aqueous extracts of bark of P. Dulce was studied for nephroprotective effect in female Wistar rats against cisplatin, gentamicin and paracetamol induced nephrotoxicity, by estimating serum creatinine, blood urea and serum albumin levels. The dried bark of P. Dulce, Roxb (Leguminosae), contains tannins, flavonoids, triterpenoids, beta-sitosterol and saponin glycoside. Treatments with the methanolic and aqueous extracts could significantly (P < 0.001) reduce the elevated serum levels of creatinine, blood urea and serum albumin. P. Dulce bark extracts significantly prevented the physical, biochemical, histological and structural changes induced by cisplatin, gentamicin and paracetamol in the kidney. The present study reports with the exploration of P. Dulce bark extracts possessed implicit nephroprotective activity. This activity may be attributed due to the abundant phytoconstituents of the plant extracts.